2005
DOI: 10.1016/j.ecss.2005.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgae response to a mercury contamination gradient in a temperate coastal lagoon (Ria de Aveiro, Portugal)

Abstract: Primary producers represent an important pathway for mercury incorporation in aquatic food webs. With eutrophication processes occurring worldwide, macroalgae may represent a substantial pool of mercury, as a result of its high growth rate and capacity to bind trace metals. The main aim of this work was to evaluate the response of the macroalgae to a human-induced environmental mercury gradient in a temperate coastal lagoon, by assessing the total and organic mercury contamination levels of the dominant specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(65 citation statements)
references
References 40 publications
3
61
0
1
Order By: Relevance
“…Research on the fate and behavior of mercury in the nearby area of the discharge has so far focused mainly on identifying the major impacted areas, quantifying the level of contamination and assessing the response of mercury to physicochemical changes in sediment and water (Pereira et al, 1998a,b). Determinations of mercury concentrations in marine biota are limited to plankton (Monterroso et al, 2003), estuarine macroalgae (Coelho et al, 2005) and sea bass (Abreu et al, 2000), hence further work is required on other species, especially edible varieties with economic interest.…”
mentioning
confidence: 99%
“…Research on the fate and behavior of mercury in the nearby area of the discharge has so far focused mainly on identifying the major impacted areas, quantifying the level of contamination and assessing the response of mercury to physicochemical changes in sediment and water (Pereira et al, 1998a,b). Determinations of mercury concentrations in marine biota are limited to plankton (Monterroso et al, 2003), estuarine macroalgae (Coelho et al, 2005) and sea bass (Abreu et al, 2000), hence further work is required on other species, especially edible varieties with economic interest.…”
mentioning
confidence: 99%
“…above discharge point) (0.08 µg.g -1 ). Various studies of coastal environments have shown that accumulation of Hg in several organisms varies along a concentration gradient of anthropogenic Hg (Coelho et al, 2005).…”
Section: Results and Discussion Weight Length And Sexmentioning
confidence: 99%
“…The tidal prism of the lagoon, for (maximum) spring tide and (minimum) neap tide, is estimated as 136.7 x 10 6 m 3 and 34.9 x 10 6 m 3 , respectively (Lopes tion (Plecha et al, 2010) or high sedimentation (Lopes and Dias, 2007), salinity variation (Almeida et al, 2005;Vaz et al, 2005), oxygen depletion (Lopes et al, 2008;Lopes and Silva, 2006) and pollutant accumulation (e.g. Pereira et al, 2005Pereira et al, , 1998a, may affect benthic foraminifera assemblages in this system. One of the most problematic factors affecting the abundance of foraminifera in Ria de Aveiro is current velocity.…”
Section: Discussionmentioning
confidence: 99%
“…These areas are also affected by chemical contaminants related to anthropic actions. In Estarreja Channel, for example, industrial and urban effluents have been discharged, for several years, by the industrial plant north of the village of Estarreja, the so-called 'Complexo Químico de Estarreja' (e.g., Pereira et al, 2009Pereira et al, , 2006Pereira et al, , 2005Pereira et al, , 1998aPereira et al, , b, 1995Válega et al, 2008;Coelho et al, 2006Coelho et al, , 2005Ramalhosa et al, 2006;Monterroso et al, 2003;Abreu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%